EFFECTIVENESS OF SOME BOTANICAL EXTRACTS ON WHEAT APHIDS - M. F. Iqbal; M. H. Kahloon; M. R. Nawaz; M. I. Javaid (Journal of Animal and Plant Sciences, 2011)
The effect of six different botanical extracts- Orange peel (Citrus sinensis); Bitter goard (Momordica dioica); Garlic (Allium vineale); Mari gold; Hot pepper (Capsicum frutescens) and Tobacco (Nicotiana tabacum) extract on wheat aphid was assessed in field at Adaptive Research Farm, Gujranwala. Wheat aphids were deliberately exposed to the above botanical extracts and then the number of live and dead aphids was counted in meter square ring on tagged spikelet’s. The botanical extracts showed varying effect on aphid population. Application of Orange Peel extract (T1) inflicted consistently the maximum level of aphid mortality (65.69%) followed by Garlic (57.91%), Tobacco (57.90%).
Keywords: Wheat aphid; Botanical extract; Pakistan